As learning systems go digital and social, can we keep up?. Issue 6 (30th September 2014) - Moore, Helena
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This case study aims to show how one award winning organization, Bromford in the UK, has engaged with and implemented multiple social media strategies that have positively impacted the very fabric and culture of the organization. Design/methodology/approach – The author shares the lessons learned in Bromford's social media journey so far – a journey that has resulted in numerous social media awards. Findings – The article describes the impact that social media has had on the organization in five areas: internal relationships; working with suppliers; leadership development; what the organization now measures; and organizational culture. Originality/value – This paper will be of value to all directors, leaders, managers and learning and development (L&D) professionals who are grappling with the rapid changes brought about by the ever-moving social media landscape. The experiences and advice of the author are shared in an accessible and practical way.